2006
DOI: 10.1111/j.1348-0421.2006.tb03806.x
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing System Lactones Do Not Increase Invasiveness of a MexAB‐OprM Efflux Mutant but Do Play a Partial Role in Pseudomonas aeruginosa Invasion

Abstract: We studied the quorum sensing (QS) system and the related homoserine lactones (HSLs) observing Pseudomonas aeruginosa invasion using the epithelial cell monolayer penetration assay model. Compared to the PAO1 wild‐type, the QS mutants, ΔlasI and ΔrhlI, were compromised in their capacity to invade. The decreased invasiveness of ΔrhlI was restored by adding 100 μM exogenous C4‐HSL. However, the decreased invasiveness of an efflux mutant, AmexAB‐oprM, was not restored in the presence of exogenous HSLs. The QS sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The role of quorum sensing (QS) and biofilm formation in Pseudomonas aeruginosa biology is clear, and previous reports have suggested that knocking out QS systems in P. aeruginosa results in decreased virulence in animal models of infection [1], [2], [3], [4], [5] and has impacts on bacterial growth rate in culture. The deletion of both the synthase genes and the responder genes for both 3-oxo-N-dodecanoyl-L-homoserine lactone (3OC12HSL) and the other principal homoserine lactone QS signal produced by P. aeruginosa , N-butyryl-L-homoserine lactone (C4HSL) should result in a quadruple knockout that will not respond to or produce 3OC12HSL or C4HSL.…”
Section: Introductionmentioning
confidence: 99%
“…The role of quorum sensing (QS) and biofilm formation in Pseudomonas aeruginosa biology is clear, and previous reports have suggested that knocking out QS systems in P. aeruginosa results in decreased virulence in animal models of infection [1], [2], [3], [4], [5] and has impacts on bacterial growth rate in culture. The deletion of both the synthase genes and the responder genes for both 3-oxo-N-dodecanoyl-L-homoserine lactone (3OC12HSL) and the other principal homoserine lactone QS signal produced by P. aeruginosa , N-butyryl-L-homoserine lactone (C4HSL) should result in a quadruple knockout that will not respond to or produce 3OC12HSL or C4HSL.…”
Section: Introductionmentioning
confidence: 99%
“…aeruginosa exports invasion determinants using theMexAB-OprM system [107]. However, the essential involvement of QSSs such as C4-HSL and 3OC12-HSL was not apparent in additional experiments, so the specific molecule involved in virulence remains unidentified [108].…”
Section: The Role Of Rnd Multidrug Efflux Pumps In P Aeruginosamentioning
confidence: 99%
“…Since the invasiveness of the mexAB-oprM -deletion mutant was restored by adding culture supernatant from MDCK cells infected with the wild-type, the authors suggested that P. aeruginosa exports invasion determinants using theMexAB-OprM system [ 107 ]. However, the essential involvement of QSSs such as C4-HSL and 3OC12-HSL was not apparent in additional experiments, so the specific molecule involved in virulence remains unidentified [ 108 ].…”
Section: The Role Of Rnd Multidrug Efflux Pumps In P Ae...mentioning
confidence: 99%